Office 365 for Healthcare Professionals Improving Patient Care Through Collaboration, Compliance, and Productivity - Dhru, Nidhish (Apress, 2018)
Healthcare is a complex, rapidly changing industry. Providers are expected to maximize and extend care for patients, while working with fewer resources and striving to stay modern and secure. This book offers prescriptive guidance and real-world use cases that will help readers leverage Office 365 and the cloud in order to be more productive, secure, and compliant with all the healthcare compliance standards. Office 365 for Healthcare increases the value of a provider's existing investment and infrastructure in Office 365 by teaching configurations and services that will resolve real day-to-day productivity and communication challenges. Understanding that each provider is unique, this book focuses on operational and clinical similarities that can be applied to any healthcare provider such as telehealth, readmission rate, shift scheduling, tumor board innovations, continuous education for medical practitioners, and more. What You'll Learn: Configure Office 365 to enable a compliant and meaningful collaboration between care providers and patients Discover innovative uses through the Tumor Board collaboration Understand specific ways to improve nurse scheduling and training Improve Telehealth for remote patients Apply simple techniques via the existing Office 365 toolset Secure Office 365 without affecting productivity Increase operating efficiency and patient satisfaction by reducing lengths of stay and re-admission This book is for IT pros, technical decision makers, and Office 365 users in the healthcare industry. Readers should have an understanding of Office 365, how healthcare organizations function, and an understanding of the technical challenges they are facing. Nidhish Dhru is a Cloud Technology Strategist at Microsoft with more than 20 years of experience in the field of technology. Nidhish helps customers across the globe overcome their business challenges with creative ideas and customize technical guidance. He is passionate about working with healthcare organizations to modernize their infrastructure, reduce operational costs, and help increase patient care via technology innovation. Nidhish presents at Microsoft Ignite and the Bay Area Healthcare Innovation Summit.